Assessing the effect of school closures on the spread of COVID‐19 in Zurich. (11th December 2022) - Bekker‐Nielsen Dunbar, Maria; Hofmann, Felix; Held, Leonhard; ,
Abstract: The effect of school closure on the spread of COVID‐19 has been discussed intensively in the literature and the news. To capture the interdependencies between children and adults, we consider daily age‐stratified incidence data and contact patterns between age groups which change over time to reflect social distancing policy indicators. We fit a multivariate time‐series endemic–epidemic model to such data from the Canton of Zurich, Switzerland and use the model to predict the age‐specific incidence in a counterfactual approach (with and without school closures). The results indicate a 17% median increase of incidence in the youngest age group (0–14 year olds), whereas the relative increase in the other age groups drops to values between 2% and 3%. We argue that our approach is more informative to policy makers than summarising the effect of school closures with time‐dependent effective reproduction numbers, which are difficult to estimate due to the sparsity of incidence counts within the relevant age groups.